CYBER-ISLAMIC MODERATION IN INDONESIA: Digital Activism of Islami.co and IBTimes.id and Its Implications for Young Muslims - Mahzumi, Fikri; Aminuddin, Ahmad; Mahfudh, Hasan; Mujibuddin SM, M. (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2025)
The digital sphere in Indonesia has evolved into a contested domain for divergent religious ideologies, particularly between radical and moderate interpretations of Islam. Over recent decades, religious radicalism has predominantly shaped the online narrative. However, the emergence of digital activism among younger generations affiliated with Nahdlatul Ulama and Muhammadiyah has led to strategic attempts at counter-narratives that emphasize religious moderation. This study investigates the role of two influential Islamic digital platforms—Islami.co and IBTimes.id—in promoting moderate Islamic discourse and shaping the religious perceptions of young Indonesian Muslims. Utilizing a mixed-methods and netnographic approach, the research integrates survey data collected from 110 university students in East Java with in-depth interviews conducted with media activists and selected platform users. The findings indicate that Islami.co and IBTimes.id are actively involved in constructing and disseminating narratives that promote Islamic moderation through curated content, strategic communication, and mission-driven digital activism. This role positions them as ideological counterbalances to radical religious narratives. The study concludes that digital media serves as a crucial platform for contemporary religious discourse and significantly influences the Islamic worldview of Indonesian Muslim youth, highlighting the importance of digital activism in promoting moderate religious values.